Perlindungan Hukum terhadap Anak sebagai Korban Cybersex Trafficking di Aplikasi Live Streaming HOT51 - Putu Sherly Chandra Sasmitha; Ni Gusti Agung Ayu Mas Tri Wulandari; Ni Nyoman Juwita Arsawati; Putu Eva Ditayani Antari (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The advancement of information technology has brought significant changes to society but also generated new crimes, such as online child sexual exploitation (cybersex trafficking). This study examines this phenomenon by focusing on the live streaming application "HOT51," which is frequently used as a medium for child exploitation. The research employs a qualitative descriptive analysis method based on secondary data from official reports and related literature. Findings indicate that the easy access to modified APK applications facilitates sexual exploitation of children, the most vulnerable group. Indonesian regulations already address child protection, but implementation faces challenges such as low digital literacy and weak supervision of digital platforms. This study emphasizes the need for tightened monitoring, digital literacy education, and active parental roles to reduce the risk of sexual exploitation in the digital realm. The contribution lies in enhancing understanding of child protection challenges in the digital era and highlighting the importance of adaptive regulations and multi-stakeholder cooperation to safeguard child rights and safety.